Peculiarities of forming the radiation situation at an area of NSC KIPT accelerators location - Dovbnya, A.N.; Mazilov, A.V.; Sosipatrov, M.V. (Вопросы атомной науки и техники, 2003)
A general problem that determines the prospects of developing the accelerator technique is to study and evaluate the influence of radiation factors on the environmental safety and biological objects. The present paper considers a complex of problems related to analysis of experimental data and investigation of the radiation situation created by NSC KIPT charged particle accelerators at an area of their location, as well as estimation of different radiation effects and their influence on the personnel and environment. Центральною проблемою, яка визначає перспективи розвитку прискорювальної техніки, є вивчення та оцінка дії радіаційних факторів на екологічну обстановку і біологічні об’єкти. В даній роботі розглядається комплекс питань, що зв’язані з аналізом експериментальної інформації та дослідженням радіаційної обстановки, яка створюється прискорювачами заряджених частинок ННЦ ХФТШ в зоні їх розташування, оцінкою впливу різних радіаційних факторів на персонал та довкілля. Центральной проблемой, определяющей перспективы развития ускорительной техники, является изучение и оценка действия радиационных факторов на экологическую обстановку и биологические объекты. В данной работе рассматривается комплекс вопросов, связанных с анализом экспериментальной информации и исследованием радиационной обстановки, создаваемой ускорителями заряженных частиц ННЦ ХФТИ в зоне их расположения, оценкой воздействия различных радиационных факторов на персонал и окружающую среду.